Diseño de una máquina de Sand-blasting para vidrio, para empresa Industrias Vitales S.A.S. (2016)
The Project was formulated and developed in this document, with the aim of designing a Sand-Blasting machine for architectural glass for the company lndustrias Vitales S.AS. Mainly, it was necessary to know all the technical characteristics and needs of the company and with this clear, a deep study was made to know the possible solutions that might be carried out, having in mind the actual techniques of this kind of process, also how is performed and managed the process in the company. With the information gathered, different proposals were proposed to sort out the problem, then selecting the best alternative based on a scoring method.